Association of dowry practices with perceived marital life and intimate partner violence - Tazeen Saeed Ali; Neesha Hussain; Shah Zeb; Asli Kulane (Journal of the Pakistan Medical Association, 2021)
Objective: To understand the perceptions of women about the influence of dowry customs on their marital life and on intimate partner violence (IPV) in a marriage. Method: This was a cross-sectional study on married women of reproductive age in Karachi, Pakistan between 2008 and 2009. Data was collected through a reliable questionnaire developed by World Health Organization, which was validated at local context and has been translated in to Urdu and then back translated in to English. Results: This study found that women whose marriages were decided conditionally on the provision of dowry to the groom’s family reported it to have had a positive impact on marital life (aOR: 11.5). Consenting to a marriage was positively associated with positive marital life (aOR: 36.8), as was the case when the marriage was contingent on dowry to be given to the groom’s family (aOR: 10.4). Provision of a dowry was not protective from physical (aOR: 3.7), sexual (aOR: 3.7), or psychological violence (aOR: 8.9). Conclusion: Dowry practices exist in Pakistani culture, despite the fact that dowry wives experience IPV. However, women perceive that the provision of dowry to groom’s family has a positive impact on marital life. In the immediate future, to protect women in and entering into marriage, there should be a strengthening of women’s organizations to provide legal, social and medical supports to women in need as well as the training of medical and paramedical professionals to recognize and respond to IPV. Continuous...